Decision Support System for Permanent Employee Appointment With the Analytic Hierarchy Process (AHP) Method at PT Pumas Rotua Gemilang Tangerang - M. Subchan; Partono Siswosuharjo; Gerardus Antonius Aryesam (Universitas Ibn Khaldun Bogor, 2023)
As time goes by PT Pumas Rotua Gemilang has experienced a lot of development with increasing production, it requires more labor, in the early days there were 200 workers until now it has reached approximately 400 workers, so the need for employee performance appraisal is needed according to company standards aims to carry out the process of assessing the feasibility of appointing employees to permanent employee status. However, the assessment is still conventional, seems slow and inaccurate, so it is necessary to have an employee appointment decision support system designed with PHP programming and mySQL as the database. The application of research using the AHP (Analytic Hierarchy Process) method the criteria used are Attendance, Knowledge, Cooperation, Work Quality and Discipline, the process begins by determining the criteria, eigenvalue. The final result of the AHP method shows the transparency of the feasibility of appointing employees with their respective values and has a certain weight according to the priorities of the company.